Utility of urinary markers in the assessment of renal dysfunction in canine babesiosis - Winiarczyk, Dagmara; Adaszek, Łukasz; Bartnicki, Michał; Abramowicz, Beata; Łyp, Paweł; Madany, Jacek; Winiarczyk, Stanisław (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2017)
Objective: Canine babesiosis is a common and clinically significant tick-borne disease caused by haemoprotozoan parasites of the genus Babesia. Acute renal failure is considered to be one of the most prevalent complications of canine babesiosis. This complication leads to a decrease in the glomerular filtration rate and in consequence causes azotemia and uremia. The objective of this study was to assess the localization and extent of renal damage in dogs infected with Babesia canis using an urinary marker for glomerular (urinary immunoglobulin G, uIgG), proximal tubular dysfunction (urinary retinol binding protein, uRBP) and distal tubular dysfunction (urinary Tamm-Horsfal protein, uTHP). Material und methods: In 10 dogs naturally infected with B. canis and 10 healthy control dogs the levels of urinary biomarkers were measured using commercially available ELISA tests. Results: Higher concentrations of uIgG, uRBP and uTHP were found in the urine of all dogs with babesiosis than in those from the control group. This indicates that in the course of the disease, the glomeruli as well as the renal tubules become damaged. Conclusion and clinical relevance: The study results allow a better understanding of the pathogenesis of canine babesiosis. However, in order to fully determine the extent and the nature of the damage to the kidneys of the infected dogs, it is advisable to conduct additional histopathological examinations of these organs.
Keywords: Babesia canis; dogs; urinary immunoglobulin G; urinary retinol binding protein; urinary Tamm-Horsfal protein